2019
DOI: 10.21608/jappmu.2019.48271
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Growth Traits and Carcass Characteristics of Abou-Delik Sheep Breed under Intensive and Semi-Intensive Management Systems in Halaieb – Shalateen - Abouramad Triangle

Abstract: Sixteen Abou-Delik male lambs, of an average live body weight 22.3 ± 3.02 kg and aged three months were used in this study to assess the effect of intensive and semi-intensive management systems on growth performance, carcass traits and economical efficiency. Lambs were randomly divided into two symmetric groups (eight lambs each) and allocated to different management systems. Lambs of group one (G1), were represent intensive management system, while, lambs of group two (G2), considered as the semi intensive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Sheep can utilize shrubs and other plant species superiorly, feed efficiency and weight gain are much better in sheep fed in open grazing as compared to confinement situations (Karim et al, 2014). The results of the current study also agree with Vargas et al (2015); Saghi et al (2015);Huma et al (2016);and Zayed et al (2019) concluded that higher bodyweight gain was observed in lambs provided open grazing and concentrate supplements than those managed indoor (stall feeding). Proper look after and management in context to supply of quality feed stuffs, nature of concentrates and management significantly improved growth rate and live weight in fattening kids (Francesco et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…Sheep can utilize shrubs and other plant species superiorly, feed efficiency and weight gain are much better in sheep fed in open grazing as compared to confinement situations (Karim et al, 2014). The results of the current study also agree with Vargas et al (2015); Saghi et al (2015);Huma et al (2016);and Zayed et al (2019) concluded that higher bodyweight gain was observed in lambs provided open grazing and concentrate supplements than those managed indoor (stall feeding). Proper look after and management in context to supply of quality feed stuffs, nature of concentrates and management significantly improved growth rate and live weight in fattening kids (Francesco et al, 2019).…”
Section: Discussionsupporting
confidence: 84%